vrkhṿt khmyfṿy mvnh ṿtṿkhn vmshnh vrkhṿt frḳ ṭ / Blessing as Mapping Reading Mishnah Berakhot, Chapter Nine - Rozen-Tsevi, Yishai (Hebrew Union College annual, 2007)
It appears that three discrete liturgical practices are discussed in Mishnah Berakhot: the Shema (Chaps. 1-3), daily prayer (Chaps. 4-5), and meal benedictions (Chaps. 6-8). However, a more thorough analysis shows that the Mishnah presents a unified liturgical system, based on reciting certain sets of benedictions at set times during the day. The only exception is Chapter Nine, the final chapter of the tractate, which presents a different and distinct type of benedictions which do not have fixed times and context but rather respond to external events or phenomena (its common formula is: "One who sees X says Y"). This type of benediction is unique and indeed unprecedented. Responsive blessings are well known already in the Bible (for example, Genesis 14:17 and Exodus 18:10), but do not receive a formal style or appear as mandatory in any pre-rabbinic or adjacent culture. The current paper discusses this phenomenon both from religious and phenomenological perspectives. Through a close reading of Chapter Nine, it discusses the problematic status of these benedictions in rabbinic liturgy, and the logic of their inclusion in Mishnah Berakhot and the liturgical system it implies. It further discusses the cosmological notions and worldview revealed in these benedictions, through their responsive characteristic. It inquires into the phenomena, natural and human, that are considered worthy of liturgical response, the grouping of these phenomena through the blessings, and, lastly, the content of the responses mandated.